(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
First critical writings by Rebecca West appeared in the magazine The Freewoman. A Weekly Feminist Review in the period 1911–1912. Her reviews were mainly focused on the contemporary literature. Criterion which Rebecca West used in order to evaluate literary works and distinguish “good” from “bad” literature was based on her strong feminist stance. First part of the article broadly discussed concepts of literary criticism and feminist literary criticism as well as the complex relationship between amateur and professional criticism at the beginning of the twentieth century. The second part examined Rebecca West’s early critical writings, in order to explore her position in the history of (feminist) literary criticism.